2015
DOI: 10.4306/pi.2015.12.4.434
|View full text |Cite
|
Sign up to set email alerts
|

Healthy and Unhealthy Dietary Patterns Are Related to Depression: A Case-Control Study

Abstract: ObjectiveMajor depressive disorder is the leading cause of disability around the world. The relationship between depression and dietary patterns has been reported in a few studies but with controversial results. This study aimed to investigate this relationship in an Iranian population.MethodsIn our study, 330 depressed patients (cases) and healthy people (controls) (1:2) were individually matched according to age, sex and area of residence. New cases of depression were recruited from two psychiatric clinics i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 44 publications
9
53
0
1
Order By: Relevance
“…It has been suggested that unhealthy dietary patterns could increase the risk of depression (Khosravi, Sotoudeh, Majdzadeh et al ., ). Robino et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested that unhealthy dietary patterns could increase the risk of depression (Khosravi, Sotoudeh, Majdzadeh et al ., ). Robino et al .…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that unhealthy dietary patterns could increase the risk of depression (Khosravi, Sotoudeh, Majdzadeh et al, 2015). Robino et al (2016) found differences in food liking and taste between general population subjects with higher and lower alexithymic scores.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…These factors portend a high risk of developing CVD. Depression has also been hypothesized as an independent risk factor for CVD and increases the associated morbidity and mortality via different mechanisms and pathways . Unhealthy dietary patterns associated with depression result in the inadequate consumption of folate, Mg, and omega‐3 fatty acids, which is a risk factor for CVD as well .…”
Section: Discussionmentioning
confidence: 99%
“…Different dietary patterns including pro-inflammatory diets have been linked to increased risk of depression [55], [56] although a recent meta-analysis highlighted the variability in findings [57]. The association between fish consumption specifically and risk of depression was recently reviewed with results from a meta-analysis concluding that high fish consumption was associated with reduced risk of depression, the pooled risk ratio of depression for the highest versus lowest consumption of fish being 0.83 (95% CI 0.74 to 0.93) [58].…”
Section: Discussionmentioning
confidence: 99%